Faktor Kesulitan Belajar Tari Jepin Tembung Panjang bagi Mahasiswa Seni Tari: Difficulty Factors in Learning Jepin Tembung Panjang Dance for Dance Arts Students - Oktariani, Dwi (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2024)
This qualitative descriptive study investigated the learning challenges faced by 50 Performing Arts education students at FKIP UNTAN in mastering the Jepin Tembung Panjang dance, a traditional Malay dance from West Kalimantan, within the Advanced Basic Malay Dance course. Utilizing interviews, documentation, and questionnaires, the research identified both internal and external factors hindering students' progress. Internal difficulties included varying levels of prior dance experience, leading to challenges in synchronizing body movements, and a lack of sensitivity to musical beats due to the use of recorded music. External challenges involved the complexities of mastering the dance's wirasa, wiraga, and wirama components, essential for professional dance competency. The research underscores the necessity of enhancing students' movement skills to elevate their dance proficiency. The findings serve as a valuable resource for evaluating current teaching methodologies and developing future solutions to optimize the Jepin Tembung Panjang dance learning experience, ensuring prospective cultural arts teachers are well-equipped with local traditional dance knowledge for their future careers.